Modified silica nanoparticles stabilized foam for enhanced oil recovery - Yin, Dandan; Li, Qiuzi; Zhao, Dongfeng; Huang, Tao (Frontiers in Energy Research, 2024)
Foam has been successfully used to improve mobility control in the process of enhanced oil recovery, yet the instability of foam limits its application. Modified nanoparticles with varying wettability were prepared by reacting 3-methacryloxypropyltrimethoxysilane (KH570) with spherical SiO2 nanoparticles in this study. Fourier transform infrared (FTIR) spectra and the measured contact angles were used to characterize the surface properties of the modified SiO2 particles, and the foam stabilization effects of wettability SiO2 were compared. Pore-scale visualization experiments were conducted using a 2D micromodel to identify the prevailing enhanced oil recovery (EOR) mechanisms of modified nano SiO2-Sodium alpha-olefin Sulfonate (AOS) foam flooding. The results indicate that modified SiO2 effectively improves foam stability by adsorbing on the bubble surface and forming a mesh-like structure. The optimum contact angle of the particles is approximately 60°, resulting in a significant increase in drainage half-life by 29.4% compared to foam stabilized only by AOS. Additionally, Foam stabilized by modified SiO2 demonstrates superior dynamic stability and deformation resistance. The modified SiO2 stabilized foam exhibits enhanced interfacial viscoelasticity and plugging and profile control performance, surpassing AOS foam in displacing more residual oil in dead-end pores. The oil recovery of the micro model was determined by ImageJ software. KH570@SiO2 (0.2wt%)-AOS (0.2wt%) foam flooding increased the recovery by 8.7% compared to AOS (0.2wt%) foam flooding.